Bcl-3: A Double-Edged Sword in Immune Cells and Inflammation - Liu, Hui; Zeng, Lin; Yang, Yang; Guo, Chunlei; Wang, Hui (Frontiers in Immunology, 2022)
The NF-κB transcription factor family controls the transcription of many genes and regulates a number of pivotal biological processes. Its activity is regulated by the IκB family of proteins. Bcl-3 is an atypical member of the IκB protein family that regulates the activity of nuclear factor NF-κB. It can promote or inhibit the expression of NF-κB target genes according to the received cell type and stimulation, impacting various cell functions, such as proliferation and differentiation, induction of apoptosis and immune response. Bcl-3 is also regarded as an environment-dependent cell response regulator that has dual roles in the development of B cells and the differentiation, survival and proliferation of Th cells. Moreover, it also showed a contradictory role in inflammation. At present, in addition to the work aimed at studying the molecular mechanism of Bcl-3, an increasing number of studies have focused on the effects of Bcl-3 on inflammation, immunity and malignant tumors in vivo. In this review, we focus on the latest progress of Bcl-3 in the regulation of the NF-κB pathway and its extensive physiological role in inflammation and immune cells, which may help to provide new ideas and targets for the early diagnosis or targeted treatment of various inflammatory diseases, immunodeficiency diseases and malignant tumors.